Prezi Media Development With A Metacognitive Approach In The Prose and Fiction Studies Course - Vina Merina Br Sianipar; Pontas J. Sitorus; Rolan Manurung; Francisco Harianto Simanjuntak (Jurnal Pendidikan, Sains Sosial, dan Agama, 2021)
This research is a development research with a modification of the Borg and Gall (2003) R&D model. This research was conducted only in the initial trial revision step (main product revision) because it was limited by time. The purpose of the research was to determine whether Prezi media with a metacognitive approach in the prose and fiction studies course could be understood and experienced improvement. The research subjects were 5th semester students in the Class of 2023 of the Indonesian Language and Literature Education Study Program. The results of the study showed that Prezi media was very good for use in the learning system with an average result of 83,75